Peran Kebijakan Strategis Inovasi Teknologi Digital dalam Transportasi Barang: Studi Perusahaan Logistik di Semarang - Kholidin; Apip (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research uses a qualitative approach with the aim of understanding phenomena about what is experienced by research subjects, for example behavior, ways of description in the form of words and language, in a special natural context and by utilizing various scientific methods, namely related to the Strategic Policy Role of Digital Technology Innovation. In Goods Transportation. The research location was at several logistics companies in Semarang, the research was conducted from July to November 2023. Data collection techniques in this research were interviews, observation, FGD/Discussion, and documentation. The data analysis technique that will be used in this research is the Interactive Model from Miles and Huberman. Data that has been collected through interviews, observation and documentation is reviewed by researchers. Next is data reduction (data reduction) where the researcher selects data to separate data that is appropriate and that is not in accordance with the research objectives. This simplified and relevant data will be used for the next steps. The research results show 1. The Important Role of Strategic Policy: Strategic policy has a key role in creating an environment that supports and encourages the adoption of digital technology in transportation. Progressive and future-oriented policies can be the main driver in changing the transportation paradigm. 2. Positive Impact of Digital Technology Innovation: The adoption of digital technology, such as the Internet of Things, artificial intelligence, and big data, can have a positive impact on operational efficiency, safety, and sustainability of transportation systems. Providing real-time data and technology integration can speed up mobility and optimize resource use. 3. Government and Private Collaboration: The successful implementation of digital technology innovation in transportation is highly dependent on cooperation between the government, private companies and other stakeholders. This collaboration can facilitate investment, share risks and accelerate the implementation of innovative solutions.